2023
DOI: 10.1002/mma.9313
|View full text |Cite
|
Sign up to set email alerts
|

Fractional modeling and optimal control strategies for mutated COVID‐19 pandemic

Abstract: As the COVID‐19 continues to mutate, the number of infected people is increasing dramatically, and the vaccine is not enough to fight the mutated strain. In this paper, a SEIR‐type fractional model with reinfection and vaccine inefficacy is proposed, which can successfully capture the mutated COVID‐19 pandemic. The existence, uniqueness, boundedness, and nonnegativeness of the fractional model are derived. Based on the basic reproduction number , locally stability and globally stability are analyzed. The sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Note that for any x 0 and x t f in R N , the adequacy and necessity condition with an external controller vector u(t) satisfying (13)…”
Section: Lemma 3 ([34]mentioning
confidence: 99%
See 1 more Smart Citation
“…Note that for any x 0 and x t f in R N , the adequacy and necessity condition with an external controller vector u(t) satisfying (13)…”
Section: Lemma 3 ([34]mentioning
confidence: 99%
“…Due to its memory and hereditary properties, fractional calculus has garnered considerable attention across various scientific fields and is widely adopted in science and engineering [13][14][15][16][17][18][19][20]. Fractional operators have been integrated into traditional complex networks, significantly improving model accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al [2] used a new nonlinear fractional-order damaged pattern with viscosity, elasticity and plasticity for rock and soil materials to characterize three-stage creep behaviors, and their pattern fully calculated and predicted the deformation with hysteresis derived from the rapid creep in tunnel engineering. Ma et al [3] developed a fractional-order model termed as SEIR type and subsequently the beingness, uniqueness, boundness of such a fractional-order system were determined. The research conclusions indicated that it is difficult for humans to avoid coexistence with the spread of the COVID-19 epidemic.…”
Section: Introductionmentioning
confidence: 99%